Correlation and Path Coefficient Analysis in Bambusa bambos (L.) Voss - Antony Joseph Raj, M.; Paramathma, M.; Kumaravelu, G. (Indian Forester, 2006)
Thirty four candidate plus clumps of Bumbusa bambos were selected from 17 locations of Tamil Nadu and assembled in the mother nursery at Forest College and Research Institute, Mettupalayam. Studies were undertaken during 1997-1999 in the mother nursery at six months after planting to elicit information on the correlation and path coefficients of Babusa bambos. The characters leading shoot length, average shoot length, number of internodes per shoot, average internodal length, average culm diameter, leaf length and leaf width were found to be poitively correlated with number of culms. Path coefficient analysis revealed that the average internodal length, leading shoot length, average shoot length, leading shoot diameter, average culm diameter have both direct and indirect effect on number of culms at six months after planting.